2007
DOI: 10.1128/iai.00482-07
|View full text |Cite
|
Sign up to set email alerts
|

I/St Mice Hypersusceptible toMycobacterium tuberculosisAre Resistant toM. avium

Abstract: We previously demonstrated that mice of the I/St strain are extremely susceptible to Mycobacterium tuberculosis, as well as to the taxonomically distant intracellular bacteria Chlamydia pneumoniae and Salmonella enterica. To broaden our knowledge about the control of susceptibility to intracellular pathogens, we studied the infection caused by Mycobacterium avium virulent strain 724 in a panel of inbred mouse strains and found that I/St mice are resistant to M. avium. By comparing I/St mice with B6 mice, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 45 publications
2
22
0
3
Order By: Relevance
“…Compared to I/St, B6 mice are considerably more susceptible to infection caused by M. avium in terms of bacterial multiplication and damage of the lung tissue: in B6, but not I/St mice prolonged infiltration with neutrophils leads to formation of necrotic lung granulomata and death [42]. The expression of igMAV_0468–0469 and igMAV_0469–0470 was very high in culture medium, only slightly lower in the lungs of susceptible, but dramatically reduced in the lungs of resistant mice (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to I/St, B6 mice are considerably more susceptible to infection caused by M. avium in terms of bacterial multiplication and damage of the lung tissue: in B6, but not I/St mice prolonged infiltration with neutrophils leads to formation of necrotic lung granulomata and death [42]. The expression of igMAV_0468–0469 and igMAV_0469–0470 was very high in culture medium, only slightly lower in the lungs of susceptible, but dramatically reduced in the lungs of resistant mice (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Two groups of 5 female I/St and B6 mice were infected with 1–2×10 3 viable CFU of M. avium in the aerosol chamber as described [42]. 13 weeks following challenge, lungs were homogenized in Trizol reagent (Life Technologies, Carlsbad, CA) and RNA was isolated according to a standard protocol using BeadBeater cell disrupter with 0.1 mm zirconia/silica beads (BioSpec Products, Bartlesville, OK).…”
Section: Methodsmentioning
confidence: 99%
“…Recently we have shown that mice of the I/St strain, which are extremely susceptible to TB [14], are resistant to M. avium infection, whereas the opposite is true for the B6 strain [15]. In agreement with data obtained by Ehlers et al [12], [13], general appearance of M. avium -induced lung granuloma in B6 mice closely resembled that of human TB lesions, but in I/St mice lung pathology was much milder and was not regularly shaped.…”
Section: Introductionmentioning
confidence: 99%
“…[10] and [16]. The airborne infected susceptible B6 mice died after 7 months, while the resistant I/St mice survived for longer than 11 months.…”
Section: Resultsmentioning
confidence: 99%